Accidental Poisoning in Children with Special Reference to Kerosene Poisoning - Dachrul Aldy; Rusdidjas Rusdidjas; Helena Siregar (Paediatrica Indonesiana, 1978)
A 6-year (1970- 1975) retrospective study of kerosene poisoning in children admitted to the General Hospital, Medan, is presented. The total number of admission was 10.643, 124 of which were kerosene poisoning. Tho mortality was 4.8%. In North Sumatera the incidence of kerosene poisoning along with the consumption of kerosene showed an increasing trend. The male to female ratio was 75 by 49 (3:2). The majority of cases were brought to the hospital within one hour after ingestion of kerosene. The presenting symptoms in the majority of cases were coughing (78.8%), vomiting (48.9%), dyspnoe 29%, fever 20.9%, brochopneumonia 12.9%, cyanosis 4.0%, and shock 1.6%. Treatment consisted of broad spectrum antibiotics, intravenous fluid, and oxygen administration. Kerosene in the household of the patients was used as fuel, either for cooking, or light source. More than 75% of the cases belonged to the lower socioeconomic class.